Pitfalls in Musculoskeletal Radiology - Peh, Wilfred C. G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This superbly illustrated book offers comprehensive and systematic coverage of the pitfalls that may arise during musculoskeletal imaging, whether as a consequence of the imaging technique itself or due to anatomical variants or particular aspects of disease. The first section is devoted to technique-specific artifacts encountered when using different imaging modalities and covers the entire range of advanced methods, including high-resolution ultrasonography, computed tomography, magnetic resonance imaging, and positron emission tomography. Advice is provided on correct imaging technique. In the second section, pitfalls in imaging interpretation that may occur during the imaging of trauma to various structures and of the diseases affecting these structures are described. Misleading imaging appearances in such pathologies as inflammatory arthritides, infections, metabolic bone lesions, congenital skeletal dysplasias, tumors and tumor-like conditions are highlighted, and normal variants are also identified. Pitfalls in Musculoskeletal Radiology will be an invaluable source of information for the practicing radiologist, facilitating recognition of pitfalls of all types and avoidance of diagnostic errors and misinterpretations, with their medicolegal implications.
Part I Imaging modality and technique pitfalls related to the musculoskeletal system -- Radiography limitations and pitfalls -- Ultrasound imaging artifacts -- Computed tomography artifacts -- Magnetic resonance imaging artifacts -- Nuclear medicine imaging artifacts -- Arthrographic techniques pitfalls -- Ultrasound-guided musculoskeletal interventional techniques pitfalls -- Musculoskeletal interventional techniques pitfalls -- Musculoskeletal biopsy pitfalls -- Errors in radiology -- Part II Regional and disease-based imaging pitfalls -- Radiographic normal variants -- Long bone trauma: radiographic pitfalls -- Spine trauma: radiographic and CT pitfalls -- Spine trauma: MRI pitfalls -- Shoulder injury: MRI pitfalls -- Shoulder injury: US pitfalls -- Elbow injury: MRI pitfalls -- Elbow injury: US pitfalls -- Wrist and hand injuries: MRI pitfalls -- Wrist and hand injuries: US pitfalls -- Hip injury: MRI pitfalls -- Hip injury: US pitfalls -- Knee injury: MRI pitfalls -- Knee injury: US pitfalls -- Ankle and foot injuries: MRI pitfalls -- Ankle and foot injuries: US pitfalls -- Pediatric trauma: imaging pitfalls -- Musculoskeletal soft tissue tumors: CT and MRI pitfalls -- Musculoskeletal soft tissue tumors: US pitfalls -- Bone tumors: radiographic pitfalls -- Bone tumors: MRI pitfalls -- Musculoskeletal tumors following treatment: imaging pitfalls -- Musculoskeletal infection: imaging pitfalls -- Inflammatory arthritides: imaging pitfalls -- Metabolic bone lesions: imaging pitfalls -- Multifocal and multisystemic bone lesions: imaging pitfalls -- Hematological and circulatory bone lesions: imaging pitfalls -- Pediatric non-traumatic musculoskeletal lesions: imaging pitfalls -- Spine non-traumatic lesions: imaging pitfalls -- Cartilage imaging pitfalls -- Bone mineral densitometry pitfalls -- Congenital skeletal dysplasias: imaging pitfalls.
Keywords: Medicine; Radiology; Orthopedics; Medicine & Public Health; Diagnostic Radiology; Orthopedics